The Protection of LGBT (Lesbian, Gay, Bisexual, Transgender) Rights According to Human Rights Perlindungan Hak-Hak LGBT (Lesbian, Gay, Bisexual, Transgender) Menurut Hak Asasi Manusia - Taebenu, Olivia J. S. (Sam Ratulangi University, 2014)
This article addresses the issue of how the development of International Human Rights Law and other legal systems of states often times undermines the acceptance of sexual orientation and gender identity that ultimately impacts on how minimum are the protection toward lesbians, gays, bisexuals, and transgenders. More concretely, this article tries to explain this issue by using international human rights law instruments such as International Covenant on Civil and Political Rights, International Covenant on Economic, Social and Cultural Rights, and other regional human rights convention such as European Convention on Human Rights and Inter-American Convention on Human Rights. Moreover, on the basis of comparison this article also uses various judicial decisions of several human rights judicial bodies such as the European Court of Human Rights and Inter-American Court of Human Rights and also judgments of several statesâ€™ Supreme Court on cases regarding the rights of LGBT where states, in their legal and religious discourses, whether directly or indirectly, often put the LGBT people as their subject of discrimination, torture and other ill-treatment, arbitrary detention, and were not granted civil liberties such as freedom of expression and freedom of association. When emphasizing substantial differences among current statesâ€™ policies and the international human rights law, this article also shows the current tendencies of states to include the LGBT people on rights that were once forbidden for the LGBT people to obtain, such as the right to adopt, right to have same-sex marriage, and right to change their biological sex by the use of medical examinations, and so on. Keywords: LGBT, homosexuality, human rights, ICCPR Â ABSTRAK Artikel skripsi ini membahas mengenai bagaimana perkembangan hukum hak asasi manusia (HAM) internasional dan sistem hukum di banyak Negara seringkali tidak sejalan dalam hal penerimaan orientasi seksual dan identitas gender yang pada akhirnya berdampak pada minimnya perlindungan terhadap kaum Lesbian, Gay, Bisexual, dan Transgender. Dalam artikel ini selanjutnya menggunakan instrumen-instrumen hukum HAM internasional seperti International Covenant on Civil and Political Rights, International Covenant on Economic, Social and Cultural Rights, dan berbagai konvensi HAM regional seperti European Convention on Human Rights dan Inter-American Convention on Human Rights. Selain itu, digunakan pula putusan peradilan dari beberapa badan peradilan HAM seperti European Court of Human Rights, Inter-American Court of Human Rights dan putusan dari Mahkamah Agung berbagai Negara sebagai perbandingan praktek-praktek hukum dan tradisi agama dalam suatu Negara, baik secara langsung maupun tidak langsung yang meletakkan kaum LGBT sebagai korban diskriminasi, penyiksaan dan perbuatan kejam lainnya, ditahan secara sewenang-wenang, dan tidak diberikan kebebasan dalam menyatakan pendapat dan kebebasan berkumpul atau berorganisasi. Seraya menekankan perbedaan antar satu Negara dengan Negara lain dalam praktek diskriminasi maupun gagalnya perlindungan hak-hak lain terhadap kaum LGBT, artikel ini juga membahas perkembangan akhir-akhir ini dimana gerakan perlindungan hak kaum LGBT mulai dicanangkan dan berdampak pada beberapa Negara mulai menyertakan kaum LGBT dalam pemberian dan perlindungan hak yang mulanya dilarang seperti hak untuk mengadopsi anak, untuk melangsungkan pernikahan sesama jenis, mengubah jenis kelamin melalui proses medis, dan lain sebagainya. Kata kunci: LGBT, homoseksual, Hak Asasi Manusia, ICCPR